Influence of spontaneous splenorenal shunts on clinical outcomes in decompensated cirrhosis and after liver transplantation. Issue 4 (9th February 2018) - Saks, Karen; Jensen, Kyle K.; McLouth, Joel; Hum, Justine; Ahn, Joseph; Zaman, Atif; Chang, Michael F.; Fung, Alice; Schlansky, Barry
Abstract : Cirrhosis and portal hypertension can lead to the formation of spontaneous splenorenal shunts (SSRS) that may divert portal blood flow to the systemic circulation and reduce hepatic perfusion. We evaluated clinical outcomes after liver transplant evaluation according to the presence or absence of SSRS at a large U.S. center. SSRS was present in 23% of 741 liver transplant candidates and did not independently predict mortality or receipt of liver transplantation, and among liver transplant recipients, SSRS did not predict post‐transplant mortality or graft failure. Abstract : Cirrhosis and portal hypertension can lead to the formation of a spontaneous splenorenal shunt (SSRS) that may divert portal blood flow to the systemic circulation and reduce hepatic perfusion. Our aims were to evaluate SSRSs as an independent prognostic marker for mortality in patients with decompensated cirrhosis and the influence of SSRSs on liver transplantation (LT) outcomes. We retrospectively analyzed adult patients with decompensated cirrhosis undergoing LT evaluation from January 2001 to February 2016 at a large U.S. center. All patients underwent liver cross‐sectional imaging within 6 months of evaluation, and images were reviewed by two radiologists. Clinical variables were obtained by electronic health record review. The cohort was followed until death or receipt of LT, and the subset receiving LT was followed for death after LT or graft failure. Survival data were analyzed using multivariable competing risk and Cox proportional‐hazards regression models. An SSRS was identified in 173 (23%) of 741 included patients. Patients with an SSRS more often had portal vein thrombosis and less often had ascites ( P < 0.01). An SSRS was independently associated with a nonsignificant trend for reduced mortality (adjusted subhazard ratio, 0.81; Gray's test P = 0.08) but had no association with receipt of LT (adjusted subhazard ratio, 1.02; Gray's test P = 0.99). Post‐LT outcomes did not differ according to SSRS for either death (hazard ratio, 0.85; log‐rank P = 0.71) or graft failure (hazard ratio, 0.71; log‐rank P = 0.43). Conclusion : Presence of an SSRS does not predict mortality in patients with decompensated cirrhosis or in LT recipients. ( Hepatology Communications 2018;2:437‐444)